Fostering community development: Utilising domiciliary physiotherapy as a tool - M. J. Futter (AOSIS, 1996)
Following a request from the Manenberg community a domiciliary physiotherapy programme was established in order to improve the quality of life of the severely disabled persons and their caregivers living in the area. Emphasis was placed on the community development process to encourage the participants to take responsibility for their own rehabilitation needs. Forty-three disabled persons were provided with rehabilitation regimens and their caregivers were trained in the physiotherapy management of their relatives until maximum benefit had been achieved. Measurements of the functional level before and after the intervention showed a significant improvement even though the injury or onset of disease had occurred from two years to eleven years previously. This improvement demonstrated that the caregivers, many of whom were functionally illiterate, were competent at performing the physiotherapy techniques required to rehabilitate their disabled relatives.